PENGARUH FAMILY CONTROL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA INDUSTRI DASAR DAN KIMIA - Kusumawati, Ivana Teddy (Business Accounting Review, 2014)
Family firms are still dominating in Indonesia,and they have advantages and disadvantages which affecting the firmâs performance. According to many previous researches about the influence of family control, there were still a lot of unconsistent results. This study aimed to know the influence of family control on profitability and firmâs value. The measurement of the profitability was measured by using ROA and firmâs value by using Tobinâs Q. The Control variables used were size, sales growth, and leverage. The sample used in this research were firms in the sector of basic and chemical industry which fulfilled certain criteria and analysed by using multiple regression analysis.The results proved that family control had no influence on profitability and firmâs value. Sales growth and leverage variables also had no influence on profitability and firmâs value. Meanwhile, size variable had positive influence on profitability and negative influence on firmâs value.